A Model Study Exploring the Decision Loop Between Unilateral Stratospheric Aerosol Injection Scenario Design and Earth System Simulations - Chenrui Diao; Patrick W. Keys; Curtis M. Bell; Elizabeth A. Barnes; James W. Hurrell (Earth's Future)
Abstract Stratospheric aerosol injection (SAI) is being discussed as a possible approach to reduce future global warming in addition to emission cuts, and numerous scenarios and Earth system model (ESM) experiments have been developed to explore its effectiveness and risks. Given the complex geopolitical, economic, and strategic considerations among countries, global cooperation in SAI deployment will be challenging. Unilateral SAI deployment has thus been highlighted as an important research topic, although it has been explored very little in scenario design and ESM studies. Inspired by a novel game theory model and a newly developed framework for identifying geopolitically plausible SAI initiator(s), this paper builds a framework for integrating unilateral SAI scenario design, geopolitical game theory, ESM simulation, and climate analyses into a single decision loop. We design and simulate a geopolitically plausible scenario of the initiation of unilateral SAI using the Community Earth System Model, and explore two independent plausible unilateral SAI reaction scenarios following the climate storylines under the initiator scenario. Our work demonstrates an approach to explore the complex feedbacks between unilateral SAI deployment scenarios and the simulation of the subsequent climate storylines.